Analisis Monitoring Emisi Sumber Tidak Bergerak di PT X di Provinsi DKI Jakarta - Muhammad Ilham Muzakki; Aussie Amalia (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The relatively high increase in economic activity and urbanization occurs in urban areas which have great potential to increase energy consumption, including the need for fuel for electricity generation. Changes in air quality have many secondary impacts on the health of humans and other organisms, the beauty of the air, the integrity of buildings and others. The purpose of this air quality monitoring activity is to find out the state of air quality and trends that may occur, examine existing pollution patterns, study the effects of air pollution on the environment, understand the processes that occur in the affected system, to determine how appropriate management and control measures are taken. air pollution and checking whether pollution control is broken. This research method uses data collection techniques in the form of qualitative and quantitative methods. Where is the quantitative method, interviews, documents and statistical data analysis. Meanwhile, judging from the two data, it can be said that it is still under control because the value is still below the threshold determined based on the Regulation of the Minister of State for the Environment No. 21 of 2008 (Appendix IV B Emission Quality Standards for Stationary Sources for PLTD) Fuel Oil.